Long‐Term Clinical Outcomes in a Cohort of Adults With Childhood‐Onset Systemic Lupus Erythematosus. Issue 2 (29th January 2019) - Groot, N.; Shaikhani, D.; Teng, Y. K. O.; de Leeuw, K.; Bijl, M.; Dolhain, R. J. E. M.; Zirkzee, E.; Fritsch‐Stork, R.; Bultink, I. E. M.; Kamphuis, S.
Abstract : Objective: Childhood‐onset systemic lupus erythematosus (SLE) is a severe, lifelong, multisystem autoimmune disease. Long‐term outcome data are limited. This study was undertaken to identify clinical characteristics and health‐related quality of life (HRQoL) of adults with childhood‐onset SLE. Methods: Patients participated in a single study visit comprising a structured history and physical examination. Disease activity (scored using the SLE Disease Activity Index 2000 [SLEDAI‐2K]), damage (scored using the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index [SDI]), and HRQoL (scored using the Short Form 36 Health Survey) were assessed. Medical records were reviewed. Results: In total, 111 childhood‐onset SLE patients were included; the median disease duration was 20 years, 91% of patients were female, and 72% were white. Disease activity was low (median SLEDAI‐2K score 4), and 71% of patients received prednisone, hydroxychloroquine (HCQ), and/or other disease‐modifying antirheumatic drugs. The vast majority of new childhood‐onset SLE–related manifestations developed within 2 years of diagnosis. Damage such as myocardial infarctions began occurring after 5 years. Most patients (62%) experienced damage, predominantly in the musculoskeletal, neuropsychiatric, and renal systems. Cerebrovascular accidents, renal transplants, replacement arthroplasties, and myocardial infarctions typically occurred at a young age (median age 20 years, 24 years, 34 years, and 39 years, respectively). Multivariate logistic regression analysis showed that damage accrual was associated with disease duration (odds ratio [OR] 1.15, P < 0.001), antiphospholipid antibody positivity (OR 3.56, P = 0.026), and hypertension (OR 3.21, P = 0.043). Current HCQ monotherapy was associated with an SDI score of 0 (OR 0.16, P = 0.009). In this cohort, HRQoL was impaired compared to the overall Dutch population. The presence of damage reduced HRQoL scores in 1 domain. High disease activity (SLEDAI‐2K score ≥8) and changes in physical appearance strongly reduced HRQoL scores (in 4 of 8 domains and 7 of 8 domains, respectively). Conclusion: The majority of adults with childhood‐onset SLE in this large cohort developed significant damage at a young age and had impaired HRQoL without achieving drug‐free remission, illustrating the substantial impact of childhood‐onset SLE on future life.